A review of Ride-Matching strategies for Ridesourcing and other similar services. Issue 5 (3rd September 2021) - Chakraborty, Jayita; Pandit, Debapratim; Chan, Felix; Xia, Jianhong (Cecilia)
ABSTRACT: Ridesourcing services have emerged as a popular alternative for commuters in metropolitan areas. There is a significant spatio-temporal variation of demand and supply for such services, which requires efficient ride-matching strategies to ensure optimal allocation of trips to drivers and users. This paper reviews different ride-matching techniques/strategies that highlight the outlook of different stakeholders, such as, drivers, users, and service providers and summarises the impacts of the matching process on the ideologies of the stakeholders. The review found that searching techniques guide the primary stakeholders like riders and drivers, and the assignment techniques ensure trip allotment. We also observed that fleet size is an important attribute to ensure availability as well as the assignment of ridesourcing services in an urban area.